A formação no Formep: repercussões na ação de supervisores de ensino - Silva, Sandro Roberto da (2020)
The following study aimed to investigate the possible contributions of the continuing education provided by the Professional Master in Education: Education training for trainers (Formep), at Pontifícia Universidade Católica de São Paulo (PUC-SP), for the Education supervisors who left the Program. It emerged from the need to identify the reasons which led the supervisors, subjects of this research, to seek Education training at Formep, to analyse the possible repercussions of the course in their lives, both in personal and professional contexts, and to investigate possible changes in their relations with other Education supervisors, with the schools, with the school community and with the State Education Department of São Paulo (SEE / SP).The main theoretical references used on Education Supervision were ALARCÃO (2010), BOLDARINE (2014), LEME (2016), MURAMOTO (1991) and SANCHEZ (2018), among other authors, in addition to official documents from SEE/SP. The theoreticalmethodological route was based on a qualitative approach (LÜDKE; ANDRÉ, 1986) and the data collection instruments used semi-structured interviews and documentary analysis (ANDRÉ, 2005).The subjects of this research were five Education supervisors, from different Education Regional Boards in São Paulo (capital) and its surroundings. The data analysis followed the assumptions of Lüdke and André (1986) for semi-structured interviews. About the possible contributions of Formep to the research subjects, the obtained results indicated that the repercussions on the Education training of the supervisor assumed a preponderant factor, since this professional achieved great changes in personal life and a personal and professional appreciation. About the repercussions of Formep in the performance of this subject, who is a supervisor, in the relations with peers, schools, the community and the State Education Department (SEE/SP), the results indicated that there were few improvements, considering the intensification of work in the daily supervision and the power relations which surround the structure of this position